SINERGI ANTARA KELUARGA, SEKOLAH, DAN GEREJA MENJADIKAN RUMAH TANGGA SEBAGAI PUSAT PAK ANAK DI MASA PANDEMI COVID-19 - Thomson Siallagan (Excelsis Deo: Jurnal Teologi, Misiologi, dan Pendidikan, 2021)
Abstract:The rapid spread of the Covid-19 pandemic has caused disruption to the Indonesian education sector where around 45 million students are unable to continue their learning activities at school. Changes in education patterns during the pandemic are very large and have important implications for education policy and implementation. During the pandemic, the house became a center for children's learning activities, including Christian religious education. The problem-solving in this article is carried out through library research by discussing several major parts, namely the importance of schools, churches, and families in synergy; the biblical basis of the family as the center of Christian religious education; the challenge of making the family the center of Christian religious education, strategies to develop synergies between schools, churches, and families to make the household the center of Christian religious education for children.Abstrak:Penyebaran pandemi Covid-19 yang cepat telah menyebabkan gangguan pada sektor pendidikan Indonesia di mana sekitar 45 juta siswa tidak dapat melanjutkan kegiatan belajar mereka di sekolah, Perubahan pola pendidikan di masa pandemi sangat besar dan memiliki implikasi penting bagi kebijakan dan pelaksanaan pendidikan. Di masa pandemi, rumah menjadi pusat kegiatan belajar anak, termasuk pendidikan agama Kristen. Pemecahan masalah pada artikel ini dilakukan melalui library research dengan membahas beberapa beberapa bagian besar yaitu pentingnya sekolah, gereja, dan keluarga bersinergi; dasar biblika keluarga sebagai pusat pendidikan agama kristen; tantangan menjadikan keluarga sebagai pusat pendidikan agama kristen, strategi mengembangkan sinergi antara sekolah, gereja dan keluarga menjadikan rumah tangga sebagai pusat pendidikan agama kristen untuk anak